الإفصاح المحاسبي والعوامل المؤثرة عليه في الشركات المساهمة السورية ( دراسة حال شركة المجموعة المتحدة للنشر والإعلان والتسويق) - زيود, لطيف; عيسى, ريم علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يجسد الإفصاح في المحاسبة عملية تقديم المعلومات الضرورية عن الوحدات الاقتصادية للأطراف ذات المصالح الحالية أو المستقبلية بتلك الوحدات. ومن هنا يعد الافصاح المحاسبي أحد أدوات الاتصال، من دون الاتصال لن تكون هناك فائدة من مخرجات النظام المحاسبي. يهدف إعداد التقارير المالية السنوية إلى تقديم معلومات عن الأنشطة المختلفة للشركة والوضع المالي لها ونتيجة أعمالها والتغييرات الحاصلة في مركزها المالي لمجموعات مختلفة من المستخدمين. وهو ما يشير إلى الدور الأساسي الذي باتت تلعبه المحاسبة كنظام للمعلومات. وقد حاولت العديد من النظريات تفسير الأسباب وراء قيام الشركات بتامين معلومات أبعد مما يفرضه عليها التنظيم. تبرز أهمية البحث في كون المعلومات أساساً وعاملاً هاماً في عملية اتخاذ القرار، وهو أمر تزداد أهميته نتيجة التطورات الاقتصادية التي تشهدها سورية في ظل الانقتاح الاقتصادي العالمي. وهذا يكسب عملية وصف وتقييم الافصاح عن المعلومات المحاسبية في التقارير المالية السنوية للشركات السورية أهمية كبيرة، عبر دراسة حالة المجموعة المتحدة للنشر والإعلان والتسويق، ورصد أهم العوامل المؤثرة فيه. Disclosure is used in accountancy as an expression of presenting necessary information about the economic units to the present and potential stakeholders. So that, accounting disclosure is one of the communication tools. Without communication, there will be no benefits from the outputs of the accounting system. The preparation of the annual financial reports is aimed to provide information on the various activities of the company, its financial position and results of its operations and all changes which may happen in its financial position for different groups of users. This refers to the basic role of the accountancy as a system for information. Thus, many theories have tried to explain why companies may provide information beyond all system limits. The importance of the research is basically raised from the fact that the information is an important factor in the decision making process, which becomes more important according to the Syrian economic developments in light of global economic openness. This will give a great importance to the description and evaluation process of the accounting information disclosure in the annual financial reports of the Syrian firms; this is by the means of the case study of the United Group of publication, advertising, and marketing, and by monitoring the most important factors influencing it.